ZnO quantum dots–decorated ZnO nanowires for the enhancement of antibacterial and photocatalytic performances. (11th September 2015) - Wu, Jyh Ming; Tsay, Li-Yi
Abstract: We demonstrate highly antibacterial activities for killing off Staphylococcus aureus and Escherichia coli using ZnO nanowires decorated with ZnO quantum dots (so-called ZnO QDs/NWs) under visible-light irradiation and dark conditions. The average size of the ZnO QDs is in the range of 3–5 nm; these were uniformly dispersed on the ZnO nanowires' surface to form the ZnO QDs/NWs. A significant blue-shift effect was observed using photoluminescence (PL) spectra. The size of the ZnO QDs is strongly dependent on the material's synthesis time. The ZnO QDs/NWs exhibited an excellent photocatalytic activity under visible-light irradiation. The ZnO QDs' active sites (i.e. the O–H bond and Zn 2+ ) accelerate the photogenerated-carrier migration from the QDs to the NWs. As a consequence, the electrons reacted with the dissolved oxygen to form oxygen ions and produced hydroperoxyl radicals to enhance photocatalytic activity. The antibacterial activities (as indicated by R -factor-inhibiting activity) of the ZnO QDs/NWs for killing off Staphylococcus aureus and Escherichia coli is around 4.9 and 5.5 under visible-light irradiation and dark conditions, respectively. The hydroxyl radicals served as an efficient oxidized agent for decomposing the organic dye and microorganism species. The antibacterial activities of the ZnO QDs/NWs in the dark may be attributed to the Zn 2+ ions that were released from the ZnO QDs and infused into the microbial solution against the growth of bacteria thus disrupting the microorganism. The highly antibacterial and photocatalytic activity of the ZnO QDs/NWs can be well implanted on a screen window, thus offering a promising solution to inhibit the spread of germs under visible-light and dark conditions.